2016
DOI: 10.1186/s12960-016-0121-z
|View full text |Cite
|
Sign up to set email alerts
|

Passing through – reasons why migrant doctors in Ireland plan to stay, return home or migrate onwards to new destination countries

Abstract: BackgroundInternational recruitment is a common strategy used by high-income countries to meet their medical workforce needs. Ireland, despite training sufficient doctors to meet its internal demand, continues to be heavily dependent on foreign-trained doctors, many of whom may migrate onwards to new destination countries. A cross-sectional study was conducted to measure and analyse the factors associated with the migratory intentions of foreign doctors in Ireland.MethodsA total of 366 non-European nationals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Contrary to the Code's recommendation on equality, Tyrell et al found that physicians trained outside of Ireland were significantly less likely to experience career progression than those trained in Ireland [12]. Brugha et al [14] found that approximately half of foreign doctors intended to migrate onwards. Most of them pointed to a lack of career progression, with twothirds planning to return home having failed to gain entry in a post-graduate training scheme [14].…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…Contrary to the Code's recommendation on equality, Tyrell et al found that physicians trained outside of Ireland were significantly less likely to experience career progression than those trained in Ireland [12]. Brugha et al [14] found that approximately half of foreign doctors intended to migrate onwards. Most of them pointed to a lack of career progression, with twothirds planning to return home having failed to gain entry in a post-graduate training scheme [14].…”
mentioning
confidence: 93%
“…Tyrell et al [13] and Brugha et al [14] add important insight on the value of career progression for retaining health workers. Contrary to the Code's recommendation on equality, Tyrell et al found that physicians trained outside of Ireland were significantly less likely to experience career progression than those trained in Ireland [12].…”
mentioning
confidence: 99%
See 3 more Smart Citations